Mood, Disability, and Quality of Life among a Subgroup of Rheumatoid Arthritis Individuals with Experiential Avoidance and Anxiety Sensitivity - S. Mehta; D. Rice; S. Janzen; J. E. Pope; M. Harth; A. P. Shapiro; R. W. Teasell (Pain Research and Management)
Objective. The current study aimed to identify and characterize distinct RA subgroups based on their level of EA and AS and compares the difference among the subgroups in mood, disability, and quality of life. Methods. Individuals with chronic pain for at least 3 months were recruited from an academic rheumatoid clinic. Participants were assessed for demographic, psychosocial, and personality measures. A two-step cluster analysis was conducted to identify distinct subgroups of patients. Differences in clinical outcomes were compared using the Multivariate ANOVA based on cluster membership. Results. From a total of 223 participants, three distinct subgroups were formed based on cluster analysis. Cluster 1 (N=78) included those with low levels of both EA and AS. Cluster 2 (N=81) consisted of individuals with moderate levels of EA and low levels AS. Cluster 3 (N=64) included those with moderate levels of EA and high AS. Compared to those in Cluster 1, those in Cluster 3 had significantly higher levels of mood impairment and disability and lower quality of life (p<0.05). Significantly lower levels of mood impairment were seen in Cluster 1 compared to Cluster 2 (p<0.05). However, no significant difference in disability or quality of life was seen between the two groups. Conclusions. The three subgroups differed significantly in levels of impairment in mood, disability, and quality of life. However, levels of EA had a greater impact on disability and quality of life than AS.